Pengaruh Permainan Ular Tangga Islami terhadap Pengenalan Akhlak Pada Anak Usia Dini - Nurita, Dian; Fajriah , Heliati; Muthmainnah, Muthmainnah (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The low recognition of moral values in early childhood requires innovative, effective, and enjoyable learning media. This study aims to determine the effect of the Islamic snakes and ladders game on early childhood moral development at TK Negeri 5 Banda Aceh. This research used a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The subjects consisted of 30 children in group B, divided into an experimental class (B1) and a control class (B2). Data were collected using an observation sheet with indicators of honesty, politeness, responsibility, and cooperation. Data analysis used an independent sample t-test after normality and homogeneity tests. The results showed a significance value of 0.000 < 0.05, indicating a significant effect of the Islamic snakes and ladders game on children’s moral recognition.